1994
DOI: 10.1002/jlb.56.2.200
|View full text |Cite
|
Sign up to set email alerts
|

13-HODE inhibits the intracellular calcium increase of activated human polymorphonuclear cells

Abstract: We studied the effect of the linoleic acid metabolite 13‐hydroxyoctadecadienoic acid (13‐HODE) on the increase of the intracellular calcium concentration, [Ca2+]i, induced by platelet‐activating factor (PAF), leukotriene B4 (LTB4), and formyl‐Met‐Leu‐Phe (fMLP) in human polymorphonuclear leukocytes (PMNs). 13‐HODE by itself did not change the [Ca2+]i of PMNs. However, when PMNs were preincubated with 13‐HODE and subsequently stimulated with PAF, LTB4, or fMLP, an inhibition of the increase of the [Ca2+]i was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The degranulatory response of PMNs to IMLP was additive on the 13-HODE-induced degranulation. In accordance, 13-HODE does not affect the fMLP-induced [Cae+]i-increase [24].…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The degranulatory response of PMNs to IMLP was additive on the 13-HODE-induced degranulation. In accordance, 13-HODE does not affect the fMLP-induced [Cae+]i-increase [24].…”
Section: Discussionsupporting
confidence: 56%
“…13-HODE attenuated the degranulatory response of PMNs to PAF. Previously, we observed a strong inhibitory effect of 13-HODE on the PAF-induced [Ca-'+]i-increase [24]. Since [Ca>]i can modulate PMN degranulation, the decrease of PAF-induced degranulation caused by 13-HODE may result from the inhibitory effect of 13-HODE on the PAFinduced [Ca2+]i.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…1C ). HODEs have been shown to play an important role in inhibition of the intracellular calcium increase 28 , induction of vasodilatation 29 , suppression of proliferation and induction of apoptosis 30 . This study showed that 13-HODE induced ER stress, perturbed lipid metabolism, and enhanced protein levels of Fas, c-CAS3, and c-PARP, leading to apoptosis and suggested that 13-HODE plays an important role in the pathogenesis of ALD.…”
Section: Discussionmentioning
confidence: 99%
“…Their results demonstrated that the highest concentration of HODE were in ALD patients [21]. HODE play an important role in increase induction of vasodilatation [22], inhibition of the intracellular calcium [23], suppression of proliferation, and apoptosis induction. Moreover, Zhang et al revealed that 13-HODE induced ER stress, perturbed lipid metabolism, and enhanced protein levels of fatty acid synthase, which progress the inflammation in the liver [24].…”
Section: Discussionmentioning
confidence: 96%